Household Water and Energy Conservation: A Key to Addressing the Water-Energy Nexus - Farooq, Safa; Kashif, Nimra; Malik, Hamna; Asif, Saher (Pakistan Journal of Humanities and Social Sciences, 2024)
Water and energy are dependent on each other. All energy production need water to work, similarly water needs energy to treat hydropower's, power plants. Recently many studies are done on water-energy nexus (Vakilifard et al., 2018). The main purpose of this study is to find locals behavior towards water and energy conservation, to teach them and aware them from upcoming challenges (Perrone, Murphy, & Hornberger, 2011). This research uses survey questionnaire methodology for collecting data about water and energy uses, conservation from Rawalpindi, Wah Cantt and Hasan Abdal.10 to 15 samples are collected from each area. By using formula, we estimated total water and energy consumption in these areas. Results shows that there are only 10% people that conserves water and 40% that conserve energy. This is because of unawareness between locals about sustainable use, lack of knowledge, not adopting modern technology (Walsh, Murray, & O’Sullivan, 2015). Findings of the research shows that locals are consuming more water and energy then conserving it. This study also highlight’s conservation barrier, future impact of inefficient water and energy use, future benefit of water and energy conservation.